Hydroxyl radical modification of collagen type II increases its arthritogenicity and immunogenicity. - Uzma Shahab (Public Library of Science (PLoS), 2012)
Background The oxidation of proteins by endogenously generated free radicals causes structural modifications in the molecules that lead to generation of neo-antigenic epitopes that have implications in various autoimmune disorders, including rheumatoid arthritis (RA). Collagen induced arthritis (CIA) in rodents (rats and mice) is an accepted experimental model for RA. Methodology/principal findings Hydroxyl radicals were generated by the Fenton reaction. Collagen type II (CII) was modified by •OH radical (CII-OH) and analysed by ultraviolet-visible (UV-VIS), fluorescence and circular dichroism (CD) spectroscopy. The immunogenicity of native and modified CII was checked in female Lewis rats and specificity of the induced antibodies was ascertained by enzyme linked immunosorbent assay (ELISA). The extent of CIA was evaluated by visual inspection. We also estimated the oxidative and inflammatory markers in the sera of immunized rats. A slight change in the triple helical structure of CII as well as fragmentation was observed after hydroxyl radical modification. The modified CII was found to be highly arthritogenic and immunogenic as compared to the native form. The CII-OH immunized rats exhibited increased oxidative stress and inflammation as compared to the CII immunized rats in the control group. Conclusions/significance Neo-antigenic epitopes were generated on (•)OH modified CII which rendered it highly immunogenic and arthritogenic as compared to the unmodified form. Since the rodent CIA model shares many features with human RA, these results illuminate the role of free radicals in human RA.